Hydroxyethyl cellulose-based indicator labels to track freshness of anchovy (Engraulis encrasicolus) - KAHRAMAN, MEMET VEZİR (WILEY, 2020)
In this study, it was aimed to develop a freshness indicator label that changes color with spoilage of fish. Hydroxyethyl cellulose-based indicator labels were prepared using two different mixed indicator (bromothymol blue/phenol red, cresol red/thymol blue) formulations. The functionality of prepared indicator labels was tested on anchovy (Engraulis encrasicolus) stored at 2 degrees C and 10 degrees C. Changes in total mesophilic aerobic bacteria, Pseudomonas spp., total yeast and mold counts, and total volatile basic nitrogen (TVB-N) contents of anchovy during storage were examined. Color changes of prepared indicator films were measured by a colorimeter. Correlation between color changes of indicator labels with microorganism growth and content of TVB-N was investigated. It is concluded that developed indicator labels change color with spoilage of anchovy and can be used as freshness indicator in fish industry.
Keywords: anchovy; fish; freshness indicator; intelligent packaging; total volatile basic nitrogen; MONITORING FRESHNESS; QUALITY CHANGES; FISH; SPOILAGE; PRODUCTS